Longitudinal Joint Experiment of Shield Tunnel Segments Reinforced with Steel Plates under Different Anchor Bolt Arrangements - WANG Jinlong; GAN Haijie; SUN Xuebing; LOU Yinghao; LIU Xian (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] To address the issues of weak interfacial bonding and unclear force transmission commonly associated with current steel plate reinforcement methods for shield tunnel segments, it is necessary to conduct full-scale experiments on the longitudinal joints (hereinafter referred to as ′joints′) of shield tunnel segments reinforced with steel plates under various anchor bolt arrangements, and to optimize existing anchor bolt configurations. [Method] A detailed description of the experimental investigation on steel plate-reinforced longitudinal joints of shield tunnel segments is delivered, covering specimen design, reinforcement methods, loading equipment, and testing/loading schemes. Ultimate bearing capacity tests are conducted on longitudinal joints subjected to different stress conditions, including positive and negative bending moments, using different anchor bolt arrangements. The mechanical performance and failure modes of the reinforced structures are comparatively analyzed to reveal their failure mechanism and evaluate the reinforcement effectiveness under different anchor bolt arrangements. [Result & Conclusion] For steel plate-reinforced shield tunnel segments subjected to positive bending moment, increasing the number of anchor bolts on both sides of the longitudinal joint could improve the joint bearing capacity by 8%. For steel plate-reinforced shield tunnel segments subjected to negative bending moments, the joint bearing capacity remains the same when reducing the number of anchor bolts on both sides of the longitudinal joint. Targeting the steel plate-reinforced shield tunnel segment joints under various anchor bolt arrangements, the bond strength is identified as the key performance indicator of the reinforcement structure.